“They test my blood to know how much blood is in my body”: the untapped potential of promoting viral load literacy to support adherence and viral suppression among adolescents living with HIV - Sarah Bernays; Joni Lariat; Frances Cowan; Beula Senzanje; Nicola Willis; Zivai Mupambireyi Nenguke (Journal of the International AIDS Society, 2023)
Abstract Introduction Achieving sustained HIV viral suppression is a key strategy to optimize the health and wellbeing of those living with HIV. Sub‐optimal adherence to antiretroviral therapy (ART) in adolescents and young people living with HIV (AYPLHIV) in Southern Africa, due to a range of social and contextual factors, including poor mental health, has presented a substantial challenge to meeting targets aimed towards improving treatment outcomes and reducing transmission. With the increasing availability of viral load (VL) testing in Southern Africa, there is an opportunity to better understand the relationship between VL literacy, wellbeing and adherence among adolescents. Methods We conducted qualitative interviews with 45 AYPLHIV aged 10–24 years in three districts (urban, peri‐urban and rural) in Zimbabwe between March and August 2021. The sample was purposively selected to represent a range of experiences related to HIV status disclosure, gender, marital status and treatment experience. Separate workshops were conducted with 18 healthcare workers (HCWs) and 20 caregivers to better understand existing support mechanisms to AYPLHIV accessing ART. We used thematic analysis to examine adolescent VL literacy, treatment support networks, experiences of clinic interactions, VL testing procedures and barriers to adherence. Results VL literacy was consistently under‐developed among participants. Comprehension of phrases commonly heard during clinic visits, such as TND (target not detected) and “high” and “low” VL, were better understood by older participants. VL testing was predominantly understood as a clinical procedure that enables HCWs to monitor treatment adherence. Absent throughout the interviews were descriptions of how viral suppression improves health and quality of life, likely fosters wellbeing and enhances self‐esteem, enables participation in education and social activities, and eliminates the risk of onward transmission. Conclusions It is imperative that we reconsider how routine VL monitoring is communicated to and understood by AYPLHIV. Reframing ART, including VL test results, in terms of the psychosocial benefits that viral suppression can generate is likely to be crucial to motivating AYPLHIV to maintain optimal treatment engagement and develop self‐management approaches as they move into adulthood. Access to accurate information tailored to individual concerns and circumstances can support AYPLHIV to achieve wellbeing.